Assessment of food safety knowledge, attitudes and practices among homebased food consumers in Kubang Pasu District / Atikah Hanani Ishak and Siti Norashikin Mohd Shaifuddin - Ishak, Atikah Hanani; Mohd Shaifuddin, Siti Norashikin (Faculty of Health Sciences, Universiti Teknologi MARA, 2023)
The COVID-19 pandemic restrictions have led to the growth of home-based online food businesses. The objective of this cross-sectional study was to assess the present status of food safety knowledge, attitudes and practices (KAP) among home-based food consumers in Kubang Pasu district. A validated, reliable online questionnaire was distributed among the community via social medial platforms. A total of 150 participants completed the questionnaire. The result showed that home-based food consumers had moderate attitudes (56.6 ±15.3) and practices (61.3 ±18.4) but have poor knowledge (49.5±14.7) of food safety. Further statistical analysis using Chisquare test revealed that gender and monthly income were the factors associated with food safety knowledge, whereas gender and current employment status were the factors associated with food safety practices(p<0.05). The study suggested that some aspects related to cross-contamination and time-temperature control should be given more attention. Therefore, awareness of food safety among home-based food consumers should be strengthened to prevent occurrence of food borne disease by taking into account the factors associated with the KAP. Food safety education should not only focus on theoretical aspects of knowledge but also positive attitudes towards food safety and promote good food safety practices.